THE CHERNOBYL ACCIDENT AND HEALTH (TWO POINTS OF VIEW) - V. M. Shubik (Радиационная гигиена, 2015)
The article presents two alternative points of view on the relationship of health malfunctions after the Chernobyl accident with radiation effect or with the factors of non-radiation nature (social, stress, nutrition peculiarities, etc.). An analysis of literature data and results of author’s own research of radiosensitive indicators of immunity condition, having essential value for the immediate and long term consequences of radiation effect was done. Possible correlation between health malfunctions of the population living in the regions, contaminated by the radionuclides, and combined effect of radiation and factors of non-radiation nature is shown.